Organizational factors, individual factors, perceived organizational support and perceived public recognition on unethical behavior among police personnel / Nusrah Samat - Samat, Nusrah (Institute of Graduate Studies, UiTM, 2017)
Ethics has been an issue of enormous interest and growing concern from time to time in most areas including in the management field. The inculcation of unethical behavior in both public and private organizations has proven to be an elusive and never ending quest. The issue of unethical conduct is also evident in Malaysia. This can be seen by the increasing frequency of coverage in media, printing and electronic, on unethical behavior and misconducts by individuals and local organizations. Unethical behaviors lead to a wide range of negative consequences. The costs associated with unethical behavior in the organization are great, estimated to be in the amount of billions annually as well as it may negatively impact the organizations’ ability to achieve sustained profitability. This will lead to financial failure and will have a deep impact on its stakeholders or might even harm the strength of the society. A study on the determinants of unethical behavior is deemed important. This will help organizations in determining which variables contribute to such behavior. Amidst the widespread concern regarding the high incidence of crimes, perceptions of corruption in the Royal Malaysia Police (RMP), and general dissatisfaction with the conduct and performance of police personnel, there is a desire to see improvements in the services provided by the police. Thus, the main purpose of this study is to investigate the antecedents of unethical behavior among police personnel as government servants…